Comparison of trauma-focused cognitive behavioral therapy and theory of mind: Improvement of posttraumatic growth and emotion regulation strategies - Vahid Farnia; Abdulzahra Naami; Yadollah Zargar; Iran Davoodi; Safora Salemi; Faezeh Tatari; Ashraf Kazemi; Behrad Basanj; Touraj Ahmadi Jouybari; Mostafa Alikhani (Wolters Kluwer Medknow Publications, 2018)
Background: Assessing various therapeutic methods with the intention to decrease the problems relevant to abused children is of high significance. Accordingly, the present study seeks to compare the effectiveness of trauma-focused cognitive behavioral therapy (TF.CBT) with an emphasis on the theory of mind on posttraumatic growth and emotional regulation strategies in abused children. Materials and Methods: This quasi-randomized clinical trial study was done on 39 abused children who referred to welfare organization centers in Ahvaz - Iran. After randomized allocation, the TF. CBT and theory of mind method were implemented for two groups. Before and after the interventions, posttraumatic growth and emotional regulation strategies were assessed with using Kilmer's posttraumatic growth inventory and Garnefski emotional regulation questionnaire. Results: The study findings indicated that the mean of the posttraumatic growth and adaptive and maladaptive emotional regulation strategies in the TF.CBT group was significantly higher than that of other study groups (P < 0.001). Conclusion: TF.CBT can lead to increased levels of posttraumatic growth and improve emotional regulation strategies in abused children. Theory of mind method can also be effective in improving emotional regulation strategies.